Do Transcortical Screws in a Locking Plate Construct Improve the Stiffness in the Fixation of Vancouver B1 Periprosthetic Femur Fractures? A Biomechanical Analysis of 2 Different Plating Constructs. Issue 1 (January 2017) - Lochab, Jasjit; Carrothers, Andrew; Wong, Edwin; McLachlin, Stewart; Aldebeyan, Wassim; Jenkinson, Richard; Whyne, Cari; Nousiainen, Markku T.
Abstract : Objectives: This biomechanical study compared Vancouver B1 periprosthetic femur fractures fixed with either a locking plate and anterior allograft strut construct or an equivalent locking plate with locking attachment plates construct in paired cadaveric specimens. Methods: After 9 pairs of cadaveric femora were implanted with a cemented primary total hip arthroplasty, an oblique osteotomy was created distal to the cement mantle. Femora underwent fixation with either: (1) a locking plate with anterior strut allograft (locking compression plating (LCP)-Allograft) or (2) a locking plate with 2 locking attachment plates (LAPs) (LCP-LAP). Construct stiffness was compared in nondestructive mechanical testing for 2 modes of compression (20 degrees abduction and 20 degrees flexion), 2 four-point bending directions (anterior–posterior and medial–lateral), and torsion. A final load to failure test evaluated the axial compression required to achieve fracture gap closure or construct yield. Fixation was compared through paired t tests (α = 0.05). Results: The LCP-Allograft construct demonstrated higher stiffness values in compressive abduction (207 ± 57 vs.151 ± 40 N/mm), torsion (1666 ± 445 vs. 1125 ± 160 N mm/degree) and medial–lateral four-point bending (413 ± 135 vs. 167 ± 68 N/mm) compared with the LCP-LAP construct ( P < 0.05). No differences were identified between the 2 constructs in compressive flexion, anterior–posterior bending, or the load to failure test ( P > 0.05). Conclusion: Use of the anterior allograft strut created a stiffer construct compared with the LCP-LAP for the treatment of a Vancouver B1 periprosthetic femur fracture only in loading modes with increased medial–lateral bending. Although these static load results are indicative of the early postoperative environment, further fatigue testing is required to better understand the importance of the reduced medial–lateral stiffness over a longer period. Abstract : Supplemental Digital Content is Available in the Text.